Pengaruh Inflasi dan Pertumbuhan Penjualan terhadap Kinerja Keuangan - Rohman Nur Rofiq; Sri Wahyuni Jamal; Muhammad Iqbal Pribadi (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
The transportation and logistics sector plays a vital role in supporting national economic growth. This study aims to analyze the effect of inflation and sales growth on the financial performance of transportation and logistics companies listed on the Indonesia Stock Exchange (IDX) for the period 2014–2024. The research method used is a quantitative approach with multiple linear regression analysis. The research sample consists of 7 companies selected through purposive sampling, resulting in a total of 77 observations. Financial performance is measured using the return on asset (ROA) indicator, while inflation and sales growth data are obtained from official sources. The results of the partial test indicate that inflation does not significantly affect financial performance, while sales growth has a positive and significant impact. These findings indicate that companies in this sector are able to manage the impact of inflation efficiently, but sales growth remains the primary factor driving profitability. The coefficient of determination shows that 28.8% of the variation in financial performance can be explained by inflation and sales growth. The implications of these research results highlight the importance of sales growth strategies to support financial performance, as well as the need for efficient management in addressing macroeconomic challenges such as inflation. This study provides empirical contributions to managerial decision-making in the transportation and logistics industry, while also filling a research gap in this sector during the post-pandemic period.